Development of e-Modules Based on Integrated Guided Inquiry TPACK (Technological Pedagogical Content Knowledge) on Chemical Equilibrium Material - Patricia Simatupang; Nora Susanti; Sardes Yosua Silaban (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
This research aims to produce an electronic module (e-module) based on the Guided Inquiry model with the TPACK approach on chemical equilibrium materials. The research method is the Research and Development (R&D) method with the Thiagarajan 4D model consisting of 4 stages, namely define, design, develop and disseminate. The instruments used were in the form of needs analysis interview sheets, student characteristics questionnaires, validation sheets by material and media experts, and teacher and student response questionnaires. The e-module is declared valid after being validated by 3 lecturers and 3 media expert lecturers. The results of the validation of the e-module by material experts obtained a feasibility percentage of 88% with the criterion of "very feasible" and the results of the validation by media experts obtained a feasibility percentage of 86% with the criterion of "very feasible". The response test was carried out on 3 chemistry teachers and 36 students from SMAN 4 Medan. Based on the results of the teacher's response, a percentage of 91.19% was obtained with the category "very interesting" and the results of the students' response were obtained a percentage of 87.47% with the category "very interesting". The results of the validation and response of the e-module show that the e-module that has been developed has been feasible and interesting to be used in the learning process. The dissemination stage in this study is limited to only disseminating e-modules without testing their effectiveness.